2015
DOI: 10.1055/s-0034-1398960
|View full text |Cite
|
Sign up to set email alerts
|

Hebephilia as a Sexual Disorder

Abstract: Hebephilia can be differentiated from pedophilia in terms of sexual interest for the body age of the minor. Associated personal distress, deviant personality characteristics as well as sexual behavior problems suggest that hebephilia can fulfill the criteria of a sexual disorder which should be considered in classification systems (DSM, ICD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 12 publications
(16 reference statements)
0
25
0
Order By: Relevance
“…Sexual crime has been identified as a "silent-violent epidemic" for more than two decades (American Medical Association, 1995), with major organizations advocating for interventions before a crime has been committed via primary and secondary prevention initiatives (e.g., Association for the Treatment of Sexual Abusers, 2011). Schemes that encourage men who are have (and are concerned about) inappropriate sexual thoughts about children to come forward for anonymous treatment and counseling, such as Project Prevention Dunkelfeld (Beier et al, 2009;Beier et al, 2016), have been found to be successful in preventing cases of sexual abuse (Beier et al, 2015).…”
Section: Sexual Crime As a Public Health Issuementioning
confidence: 99%
“…Sexual crime has been identified as a "silent-violent epidemic" for more than two decades (American Medical Association, 1995), with major organizations advocating for interventions before a crime has been committed via primary and secondary prevention initiatives (e.g., Association for the Treatment of Sexual Abusers, 2011). Schemes that encourage men who are have (and are concerned about) inappropriate sexual thoughts about children to come forward for anonymous treatment and counseling, such as Project Prevention Dunkelfeld (Beier et al, 2009;Beier et al, 2016), have been found to be successful in preventing cases of sexual abuse (Beier et al, 2015).…”
Section: Sexual Crime As a Public Health Issuementioning
confidence: 99%
“…The Dunkelfeld Project aims to offer early intervention (via psychological and psychiatric treatment) in an attempt to prevent child sexual abuse before it occurs. Early evidence of the effectiveness of the Dunkelfeld Project comes from small-scale studies of the interventions that are offered, with data indicating reductions in the expression of offense-supportive cognitions (Amelung, Kuhle, Konrad, Pauls, & Beier, 2012), and improved sexual self-regulation (Beier et al, 2015).…”
Section: Progressive Responses To Sexual Offendingmentioning
confidence: 99%
“…Applying a non-randomized waiting list control design, a treatment group and control group were assessed before and after a twelve-month treatment/waiting period, respectively. Withingroup and between-groups comparisons were conducted to evaluate treatment change (Beier et al 2015).…”
Section: First Results From the Prevention Project Dunkelfeld (Ppd)mentioning
confidence: 99%